Citizen insecurity and its incidence in business management - Centeno Cárdenas, Josué Giraldo (2018)
Objective: To find the incidence of citizen insecurity in the development and management of companies and how the decrease in productivity and increase in production costs have been affected in the last 5 years. Method: This is a quantitative research of an exploratory, transversal and correlational type. It is of a non-experimental nature, and makes use of instruments for statistical analysis. 90 small and medium-sized companies and 97 micro-enterprises have been sampled. Results: The collected samples indicate that the perception of insecurity is increasing and that its impact on investments and business development is worrisome. Conclusions: A greater commitment of the State is necessary, as well as the trade union organizations to contribute in a decisive manner in reducing this increasing overall insecurity.